Impacto nutricional da inclusão de extrato tanífero de acácia negra (Acacia mearnsii) na dieta de ovinos e vacas em lactação - Orlandi, Tiago (2016)
This study aimed to evaluate the effect of tannin extract from Acacia mearnsii in the reduction of total and urinary nitrogen (N) excretion, in optimizing nutritional and productive performance of lactating cows grazing on temperate or tropical pastures, and also aimed to evaluate its effects on the digestive process, N excretion as well as the flow of metabolites through the portal system and liver of sheep fed temperate grass or tropical grass based diets. Four assays were carried out, two with sheep and two with lactating cows. In assay 1, six sheep were used in a crossover design for two 21-day periods to evaluate the intake, digestibility and N excretion. The diets were composed of Tifton hay 85 and concentrate either without the inclusion of tannin extract (control) or with the addition of 1% tannin extract (dry matter (DM) basis). In assay 3, five sheep were used in a crossover design for two 21-day periods to evaluate the intake, digestibility, N excretion and the flow of blood metabolites through the portal system and liver. The diets were a mixture of oats and ryegrass hay and concentrate either without the addition of tannin extract (control) or with the addition of 2% tannin extract. In assays 2 and 4 were used 14 lactating cows in each assay through a random block design. The experiments lasted for 49 days, and were divided into two periods. In the first 21 days all cows received, for standardization, the same diet and were later randomly assigned, within each block, one of the treatments. In experiment 2, cows were grazing on Tifton 85 pasture and supplemented with concentrate containing 1%, or not (control), of tannin extract. In experiment 4, the cows were kept in mixed oats and ryegrass pasture, and supplemented with concentrate either with the addition of 2% tannin extract or without (control) the addition of tannin extract. For the sheep assays were collected food, scraps, feces, urine and samples as well as arterial, liver and portal blood samples, for assay 3. For assays with cows were collected food scraps, feces, urine and milk samples as well as blood samples from the coccygeal vein. The data were submitted to variance analysis and the effect of treatment compared by F test using the SAS statistical program. P≤0.05 values were considered significant and 0.05<P≤0.10 were considered trend. In assay 1 the inclusion of tannin in the diet promoted a reduction in the true digestibility of N and endogenous N excretion (P≤0.05), without affecting consumption, fecal and urinary excretion of N and digestibility of other dietary fractions (P>0.05). In assay 2 the tannin extract did not cause any changes (P>0.05) in consumption, and milk yield or composition, or the N use efficiency for synthesis of milk proteins, as well as in plasma urea concentrations. There was, however, an increase in N excretion via urine and hence reduction in the overall N use efficiency. In assay 3 there was a reduction (P≤0.05) of the true and apparent N digestibility and urea excretion by urine without affecting the parameters of intake, digestibility of organic matter, neutral detergent fiber and synthesis of microbial rumen nitrogenous compounds. The N-urea concentrations in arterial, portal and hepatic blood samples reduced (P≤0.05) and hepatic glucose concentration tended to decrease (P=0.065) due to the intake of the tannin extract. However, there was a reduction in N-urea flow only in total visceral tissue (P=0.053), and neither concentrations nor the N-NH3 flow changed (P>0.05). In assay 4 the intake of tannins did not affect any milk yield and composition parameters, neither plasma concentrations of urea. It did, however, promote increase (P≤0.05) pasture intake and fecal N excretion and tended to decrease (P≤0.10) N excretion through urine without altering the N use efficiency. The inclusion of 2% tannin extract of Acacia mearnsii in the concentrate fed to dairy cows in the proportion of approximately 25% of the diet based on temperate grasses promotes increased fodder consumption and has the potential to reduce the environmental impact due to the reduction of urinary N excretion, without short term interference in milk yield and composition. Furthermore, based on the study with sheep, offer of up to 40% of concentrate in the diet promotes a more marked reduction in urinary N excretion and may have positive effects on the concentrations of urea in milk and plasma. In assays with tropical grass the inclusion of tannin in the diet did not show results that justify the use of this additive in the assessed dietary conditions.